Implantación del proceso contable por órdenes de producción en la “ASOCIACIÓN DE PRODUCCIÓN REINA DEL CISNE LOJA, ASOREILOJ” de la ciudad de Loja, periodo del 01 de octubre al 31 de diciembre del 2017 - Riofrio Labanda, Viviana Eloisa (2018)
The thesis work entitled "IMPLEMENTATION OF THE ACCOUNTING PROCESS FOR PRODUCTION ORDERS IN THE" QUEEN OF THE CISNE LOJA, ASOREILOJ PRODUCTION ASSOCIATION "OF THE CITY OF LOJA, PERIOD FROM 01 OCTOBER TO DECEMBER 31, 2017", was developed with the purpose of knowing the financial and economic situation of the Association as well as knowing the unit costs of each one of the garments, household items and school kits and making the most appropriate decisions for their development and growth. As a first instance, the Initial Inventory of assets and rights was drawn up through physical verification, which allowed knowing the inventories and their capital, a situation that made it possible to determine the Asset and Patrimony of the "Queen of the Swan Production Association". ASOLEILOJ "to October 1, 2017, and which served in the later for the preparation of the Initial Situation Statement, and start the accounting record. In a second moment, the Accounts Plan was structured according to the needs and policies of the Association, chronologically, duly ordered and codified, both the patrimonial accounts and the results, which served as the basis for the realization of the Accounts Manual that includes the description, movement and balance of each of the accounts that make up 5 the Plan, elements that served as a basis and guide for the application of the accounting process. In a third moment, the main accounting records were drawn up, which are applicable in all the accounts, among them the General Journal, the Major, Verification Balance and Worksheet; In the same way, auxiliary records were designed, including order of production, requisition of materials, watch cards among others that allow to know exactly the real value of the raw material and labor used, as well as the valuation and distribution of the real unit and total production costs and on the basis of which a sale price can be set that allows it to establish reasonable surpluses and thus raise the level of production. Fourth and last moment, we proceeded to the preparation and presentation of the Financial Statements, starting with the State of Production Costs Sold, the Income Statement, the Statement of Financial Position, and finally the Statement of Cash Flow, which allowed know the real economic and financial situation of the Association.